Reliability and maintainability in photovoltaic inverter design - Ma, Z J; Thomas, S (2011 Proceedings - Annual Reliability and Maintainability Symposium, 2011)
This paper focuses on how to ensure high reliability and long service life of photovoltaic (PV) inverters in the design phase. First, a standard usage model of inverters is proposed based on the study of the application environment in U.S.A. Then, the main failure mode, stress level, and useful life of critical components in inverters are analyzed. Finally, a proactive maintenance plan for long-term reliability of PV inverters is discussed.